1991
DOI: 10.1172/jci115325
|View full text |Cite
|
Sign up to set email alerts
|

An epoxygenase metabolite of arachidonic acid mediates angiotensin II-induced rises in cytosolic calcium in rabbit proximal tubule epithelial cells.

Abstract: Previous studies from this and other laboratories have shown that angiotensin II (AII) induces [Ca2"j transients in proximal tubular epithelium independent of phospholipase C. AII also stimulates formation of 5,6-epoxyeicosatrienoic acid (5,6-EET) from arachidonic acid by a cytochrome P450 epoxygenase and decreases Na' transport in the same concentration range. Because 5,6-EET mimics AII with regard to Na' transport, its effects on calcium mobilization were evaluated. ICa2i, was measured by video microscopy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
65
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 37 publications
8
65
1
Order By: Relevance
“…Our previous results suggest that the link to CIF requires the activation of cPLA 2 and release of arachidonic acid from cellular phospholipids in U937 cells (8). Other groups have reported similar correlations between arachidonic acid release and calcium influx (43,44). Cytochrome P450 activity has also been coupled to the formation of CIF (45,46) and is one of the major pathways through which arachidonic acid is metabolized.…”
Section: Discussionmentioning
confidence: 68%
“…Our previous results suggest that the link to CIF requires the activation of cPLA 2 and release of arachidonic acid from cellular phospholipids in U937 cells (8). Other groups have reported similar correlations between arachidonic acid release and calcium influx (43,44). Cytochrome P450 activity has also been coupled to the formation of CIF (45,46) and is one of the major pathways through which arachidonic acid is metabolized.…”
Section: Discussionmentioning
confidence: 68%
“…Similarly, we also failed to detect a significant cell Ca 2+ increase in the presence of 10 − 7 mol/L arachidonic acid ( n = 8). On the other hand, Douglas and colleagues also reported that incubating a cell culture with arachidonic acid significantly enhances the Ang II-induced cell Ca 2+ increase ( 24 ). As shown in Fig.…”
Section: +mentioning
confidence: 81%
“…Douglas and colleagues, however, reported different mechanisms for cell Ca 2+ increase. On the basis of data obtained from cultured rabbit proximal tubular cells, they proposed that Ang II-induced Ca 2+ increases in proximal tubules arise secondary to the release of arachidonic acid and the production of 5,6-EET ( 24 ). To test whether a similar mechanism operates in intact proximal tubules, we measured cell Ca 2+ concentrations in wild-type mice.…”
Section: +mentioning
confidence: 99%
“…Earlier studies have shown that the CYP epoxygenase products of AA, such as 5,6-, 8,9-, 11,12-, and 14,15-epoxyeicosatrienoic acids, inhibit platelet-derived growth factor-BB-induced and serum-induced VSMC motility (40). To understand whether AA-induced VSMC motility requires its conversion via the CYP epoxygenases, we next studied the effects of SKF525A and ketoconazole, two potent and specific inhibitors of this enzymatic pathway (40,41). Neither SKF525A (100 mM) nor ketoconazole (20 mM) inhibited AA-induced VSMC motility (Fig.…”
Section: Resultsmentioning
confidence: 99%